Knowledge, Attitudes and Skills of Science Teachers Regarding ICT in West Sumatra - Har, Erman; Taula Sari, Rona (KnE Social Sciences, 2022)
The objectives of this research were to study the differences in teachers’ knowledge of ICT based on schools’ location and teachers’ working experience, and to observe the relationship between teachers’ skills and attitudes about ICT. Participants were science teachers who worked in West Sumatra and purposive sampling was used. Data were analyzed using t-test and one-way ANOVA, and correlation product moment assessment was also employed. There was a significant difference between the knowledge of science teachers who taught in urban vs. rural areas (t = 3.15, p = 0.002); teachers who taught in urban areas had more knowledge about ICT compared with those who taught in rural areas. Moreover, there were differences in science teachers’ knowledge about ICT depending on their working experiences (t = 1.82, p = 0.07). Science teachers’ attitude about ICT had a weak and positive correlation with their skills in utilizing ICT. It can be concluded that prerequisites for learning science with the use of ICT are computer hardware, internet access, and training facilities in order to improve teachers’ knowledge on ICT, particularly experienced teachers. Keywords: ICT knowledge, ICT skills, science teachers, school location, work experience